Pemertahanan Prapen Pada Masyarakat Soroh Pande di Desa Tejakula Kecamatan Tejakula Kabupaten Buleleng - Made Hermawati Diah Pertiwi; Ni Luh Gede Hadriani; Putu Mardika (Kamaya: Jurnal Ilmu Agama, 2026)
Prapen is a cultural heritage of the Soroh Pande community that historically functioned as a traditional blacksmithing workshop for metal processing. Along with technological advancements and social changes, its practical function has gradually declined. Nevertheless, the Soroh Pande community in Tejakula Village, Tejakula District, Buleleng Regency continues to preserve prapen as an essential symbol of cultural identity and ancestral heritage. This study aims to analyze the form and structure of prapen, the efforts undertaken to preserve it, and the meanings it holds for the Soroh Pande community. This research employed a qualitative descriptive approach. Data were collected through observation, interviews, documentation, and literature review, and were analyzed using data reduction, data display, and conclusion drawing. The findings reveal that the form and structure of prapen continue to reflect the principles of traditional Balinese architecture based on the Tri Angga concept while embodying a sacred dimension associated with the worship of Dewa Brahma. Preservation efforts are carried out through the physical maintenance of the structure, the implementation of religious rituals, its continued use in customary activities, and the transmission of cultural values to younger generations. Beyond its original function as a blacksmithing workshop, prapen has become a symbol of the genealogical identity of the Soroh Pande, a medium for cultural transmission, and an expression of respect for ancestors. This study concludes that prapen constitutes an integral part of the cultural system of the Soroh Pande community, encompassing historical, religious, social, and symbolic values. Its preservation plays a significant role in safeguarding cultural identity and ensuring the sustainability of ancestral cultural heritage amid the challenges of modernization.